The association between alcohol consumption and self-reported current depression among adults residing in Brazil. (26th December 2020) - Oancea, S C; de Oliveira, G D; Sukumaran, P; Vogeltanz-Holm, N; Nucci, L B
Abstract: Background: The purpose of the current study was to investigate the association between binge and heavy drinking and self-reported current depression (SRCD) in a representative population-based sample of adults residing in Brazil. Methods: The sample for this study was based on the 2013 Brazilian National Health Survey. SRCD was accessed using the Patient Health Questionnaire (PHQ-8), a valid eight-item depression measure for population-based studies instrument. The association between binge/heavy drinking and SRCD was investigated using weighted and adjusted multivariable logistic regression models. Results: Out of the final study sample of 59 399 Brazilians, 47.2% were young adults, 34.6% were middle age adults and 52.4% were females. The prevalence of binge drinking was 13.8%, of heavy drinking was 3.2% and SRCD was 7.6%. There was a significant weighted and adjusted association between binge drinking and SRCD among young and middle age females (OR = 1.5, 95% CI:1.1–2.0 and OR = 0.6, 95% CI:0.4–0.8, respectively) and between heavy drinking and SRCD among young and middle age males (OR = 1.8, 95% CI:1.2–2.8 and OR = 2.5, 95% CI:1.5–4.1, respectively). Conclusions: The possible protective factor of binge drinking for SRCD among middle-aged Brazilian females needs to be further investigated and understood. Longitudinal research is needed to provide further evidence of associations found in this study.